A Highly Energetic N‐Rich Zeolite‐Like Metal‐Organic Framework with Excellent Air Stability and Insensitivity. Issue 12 (7th August 2015) - Qin, Jun‐Sheng; Zhang, Ji‐Chuan; Zhang, Min; Du, Dong‐Ying; Li, Jing; Su, Zhong‐Min; Wang, Yuan‐Yuan; Pang, Si‐Ping; Li, Sheng‐Hua; Lan, Ya‐Qian
Abstract : A stable N‐rich aromatic ligand is employed to prepare energetic zeolite‐like metal‐organic frameworks.IFMC‐1 shows excellent air stability, and the lowest sensitivity toward impact, friction, and electrostatic discharge and the highest predicted heat of detonation among the reported coordination polymers, and even commercial materials (such as trinitrotoluene (TNT)).